PENYELESAIAN SENGKETA PADA LEMBAGA KEUANGAN OLEH BADAN PENYELESAIAN SENGKETA KONSUMEN DI KOTA PEKANBARU - Miftahul Haq (Ensiklopedia Sosial Review, 2025)
Abstract: The consumer dispute resolution process based on the Consumer Protection Law can be achieved through litigation and non-litigation channels. Settlement through non-litigation channels is carried out by BPSK through Mediation, Conciliation, and Arbitration. BPSK cannot play an active role in resolving consumer disputes, this is because the substance of the regulations, procedures and mechanisms for dispute resolution contain many weaknesses. Consumer protection is essentially all efforts that guarantee the fulfillment of the rights and obligations of consumers and business actors as well as ensuring legal certainty, efforts to resolve consumer disputes through BPSK face problems including: too complex tasks because it functions as a consumer dispute resolution institution and includes guidance and supervision. The absence of clear regulations regarding budget allocation. Lack of human resources for BPSK members, and low legal awareness of consumers and business actors.Keywords: Consumer Protection, BPSK, Dispute Resolution